Analisis Yuridis Terhadap Perbuatan Mark-up Oleh Panitia Pengadaan Barang Dan Jasa Dalam Proyek Pemerintah - Rika Susilawaty; Triono Eddy; Alpi Sahari (Mahesa Research Center, 2020)
The influence of the development of the strategic environment as well as the influence of the actors' motivational aspects, policy aspects or aspects of law enforcement, has influenced the increase in smuggling, both smuggling imports and export smuggling, increasing cases of smuggling, particularly smuggling of imports, has caused various impacts, especially the decline in the competitiveness of domestic production in the market which will ultimately also affect the improvement of the national economy. The research conducted is a descriptive study with a normative legal approach (normative juridical) conducted by means of literature study. Data collection tools used in this study are data in the form of document studies and literature searches. which become the knife of analysis in this study are theories of legal certainty, theories of criminal liability, and theories of criminal law policy. Sanctions given by the Panel of Judges against the defendant do not describe justice and order in the community, because the sentence tends to be mild and does not give a deterrent effect on the perpetrators of corruption. Efforts to deal with crime with criminal law (a means of punishment) and more emphasis on the nature of